The real contact width evaluation of a three-layer metal gasket - I Made Gatot Karohika; Shigeyuki Haruyama (Universitas Mercu Buana, 2022)
The performance of a three-layer metal gasket is affected by the contact width between the gasket surface and the rough flanges. In the simulation, proper flange roughness modeling will make it easier to predict the gasket performance later. The surface roughness modeling in the simulation will be compared with experimental measurements to determine how much contact occurs due to the rough flange surface. Experimental measurement of real contact width using a digital microscope and simulation using finite element software. The measurements between the simulation results of the real surface roughness model and the experimental results show that they are close to the same. So it can be said that our simulation model is close to the actual conditions.